Monoesterase activity of a purple acid phosphatase mimic with a cyclam platform - Comba, Peter; Zajaczkowski-Fischer, Marta (Chemistry - a European journal, 2012)
The synthesis and characterization of a novel dinucleating ligand L (L=4,11-dimethyl-1,8-bis2-[N-(di-2-pyridylmethyl)amino]ethylcyclam) and its μ-oxo-bridged diferric complex [(H2L)FeIII2(O)(Cl)4]2+ are reported. This diiron(III) complex is the first example of a truly functional purple acid phosphatase (PAP) mimic as it accelerates the hydrolysis of the activated phosphomonoester 2,4-dinitrophenyl phosphate (DNPP). The spectroscopic and kinetic data indicate that only substrates that are monodentately bound to one of the two ferric ions can be attacked by a suitable nucleophile. This is, most probably, a terminal iron(III)-bound hydroxide. DFT calculations support this assumption and also highlight the importance of secondary interactions, exerted by the protonated cyclam platform, for the positioning and activation of the iron(III)-bound substrate. Similar effects are postulated in the native enzyme but addressed in PAP mimics for the first time.
Gesehen am 22.08.2018